Prognosticating autoimmune encephalitis: A systematic review. (January 2019) - Broadley, James; Seneviratne, Udaya; Beech, Paul; Buzzard, Katherine; Butzkueven, Helmut; O'Brien, Terence; Monif, Mastura
Abstract: Objective: To perform a systematic review of the current scientific literature in order to identify variables associated with patient prognosis in autoimmune encephalitis. Methods: We performed a systematic literature search using MEDLINE, Embase, PubMed and PsychInfo databases. We selected studies that explored the correlation between early clinical and paraclinical findings, and patient outcomes. Data was extracted, analyzed and recorded in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Results: Forty four publications detailing 2823 subjects matched our inclusion criteria. There was considerable heterogeneity in methodology, patient profile, investigation results and clinical outcome measures. Findings were often discrepant for cases of anti-NMDAR encephalitis when compared with other causes of autoimmune encephalitis. Delay in immunotherapy contributed to a variety of worse outcomes for patients with different subsets of autoimmune encephalitis. Altered consciousness, ICU admission and no use of immunotherapy were variables associated with poor prognosis in anti-NMDAR encephalitis. Older age, sex, the presence of status epilepticus, CSF abnormalities and MRI changes were unlikely to have significant prognostic value. The influence of antibody titers, autonomic dysfunction and underlying malignancy was unclear. Conclusions: A number of variables were identified to have potential predictive value for outcomes in autoimmune encephalitis. Heterogeneous study design, size and quality were major limiting factors in this review. Highlights: This review examines predictive variables of prognosis in autoimmune encephalitis. Delayed immunotherapy is associated with a wide variety of poor outcomes. Some variables had clear associations with outcomes only in anti-NMDAR encephalitis. The associations of several other variables with outcomes are unclear.